Generación de energía eléctrica hasta 1000 watts con el empleo de un sistema hidraúlico para utilizar en una vivienda del Cantón Lago Agrio - Mera Cueva, Cristian Rolando (2016)
The Project entitled grade “Power generation up to 1000 watts with employment of a hydraulic system for use in a house in the canton Lago Agrio” consists in to construction of a hydraulic system for generating electrical energy, since of a mechanic impulsor type hydraulics Wheel, with capacity of 1000 watts, in property of Cueva Cevallos Víctor Gribaldo located in Lago Agrio city – Sucumbíos. This integrated system for dam, hydraulic wheel, tubing and generator, allows harness hydraulic energy produced for a constant level of dammed water, which flows in a tubing flowing reducing its diameter by a nozzle, causing the release of water of high speed collided with the blades of hydraulic wheel allows permanent rotation of this, which in turn is coupled through its axle to a generator and thus the mechanical energy is converted in electrical energy. The parameters used in the design: Flow (6,25 l/s), revolutions per minute in hydraulic wheel (42 rpm); speed multiplier - ratio (1:23), electric power generating (1000 watts), to replace generator motor of 950 watts. The methodology for the development of this project was the experimental, which consists in a systematic process and a scientific to research, where the investigator manipulates one or more variables, controls and measuring any chance in others variables. And the scientific methodology, which is the systematic observation, measurement, experimentation, formulation, analysis and modification of the hypothesis initially raised.